Step-by-step explanation:
![4\frac{9}{20} - 1\frac{2}{6} =\\\frac{89}{20} - \frac{8}{6} = \frac{89 - 26.7}{20} = \frac{62.3}{20} \\](https://tex.z-dn.net/?f=4%5Cfrac%7B9%7D%7B20%7D%20-%201%5Cfrac%7B2%7D%7B6%7D%20%3D%5C%5C%5Cfrac%7B89%7D%7B20%7D%20%20-%20%5Cfrac%7B8%7D%7B6%7D%20%3D%20%5Cfrac%7B89%20-%2026.7%7D%7B20%7D%20%3D%20%5Cfrac%7B62.3%7D%7B20%7D%20%5C%5C)
![4\frac{6}{9} - 3\frac{3}{6} =\\\frac{42}{9} - \frac{21}{6} = \frac{252 - 189}{54} = \frac{63}{54} = 1\frac{9}{54}](https://tex.z-dn.net/?f=4%5Cfrac%7B6%7D%7B9%7D%20%20-%203%5Cfrac%7B3%7D%7B6%7D%20%3D%5C%5C%5Cfrac%7B42%7D%7B9%7D%20-%20%5Cfrac%7B21%7D%7B6%7D%20%3D%20%5Cfrac%7B252%20-%20189%7D%7B54%7D%20%3D%20%5Cfrac%7B63%7D%7B54%7D%20%3D%201%5Cfrac%7B9%7D%7B54%7D)
![2\frac{2}{4} - 1\frac{1}{3} =\\\frac{10}{4} - \frac{4}{3} = \frac{30 - 16}{12} = \frac{14}{12} = 1\frac{2}{12}](https://tex.z-dn.net/?f=2%5Cfrac%7B2%7D%7B4%7D%20-%201%5Cfrac%7B1%7D%7B3%7D%20%3D%5C%5C%5Cfrac%7B10%7D%7B4%7D%20-%20%5Cfrac%7B4%7D%7B3%7D%20%3D%20%5Cfrac%7B30%20-%2016%7D%7B12%7D%20%3D%20%5Cfrac%7B14%7D%7B12%7D%20%3D%201%5Cfrac%7B2%7D%7B12%7D)
Answer:
.5? or 1/2
Step-by-step explanation:
i think its half, because the Y factors are going down by half.
i hope that kinda made sense.
Answer:
- 819
Step-by-step explanation:
The sum to n terms of a geometric series is
= ![\frac{a(r^n-1)}{r-1}](https://tex.z-dn.net/?f=%5Cfrac%7Ba%28r%5En-1%29%7D%7Br-1%7D)
where a is the first term and r the common ratio
Here a = 1 and r = - 4 ÷ 1 = - 4, thus
=
=
=
= - 819
No no no no no no no no no no no no no no no no no